UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING DENGAN PEMANFAATAN MEDIA QUIZIZZ SISWA KELAS V PADA MATERI BANGUN RUANG DI MI ISLAMIYAH 01 KOTA MADIUN - Subekti Hery Cahyo Saputro; Tegar Riski Pratama; Taufik devanto; Melik Budiarti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aimed to improve the cognitive learning outcomes of fifth-grade students at MI Islamiyah 01 Madiun City in spatial geometry by implementing Problem-Based Learning (PBL) with the aid of Quizizz. The method used was Kurt Lewin's Classroom Action Research (CAR), which encompasses planning, action, observation, and reflection. Thirteen students participated in the study. Data were collected through observation, tests, documentation, and interviews. Results from the pre-cycle phase indicated that some students still scored below the Minimum Completion Criteria (KKM), with a completion percentage of 7.69%. In the first cycle, completion increased to 38.5%, although it did not meet the target. Through learning improvements in the second cycle, all students successfully met the KKM (100%) with an average score of 86.53. The application of PBL and Quizizz has been shown to improve students' understanding of spatial geometry concepts, making learning more contextual and enjoyable. Therefore, this approach has proven effective in improving student learning outcomes in mathematics and is recommended for use in teaching concrete materials.